A meta-analysis of periodized versus nonperiodized strength and power training programs - Rhea, M. R.; Alderman, B. L. (Research Quarterly for Exercise and Sport, 2004)
The purpose of this study was to quantitatively combine and examine the results of studies examining the effectiveness of periodized (PER) compared to nonperiodized (Non-PER) training programs for strength and/or power development. Two analyses were conducted to (a) examine the magnitude of treatment effect elicited by PER strength training programs compared to Non-PER programs and (b) compare these effects after controlling for training volume, frequency, and intensity. Studies meeting the inclusion criteria were coded based on characteristics that might moderate the overall effects (i.e., participant characteristics and characteristics related to the training program). Effect sizes (ESs) were calculated for each study, and an overall ES of 0.84 (± 1.41) favoring PER training was found. Further analyses identified the treatment effect specific to training variation to be ES = 0.25. Significant moderating variables included age, training status, and length of training program. As a result of this statistical review of the literature, it is concluded that PER training is more effective than Non-PER training for men and women, individuals of varying training backgrounds, and for all age groups. In line with the overload principle, additions to volume, intensity, and frequency result in additional training adaptations.